(untitled) (Nepalese Journal of Zoology, 2020)
Ants are one of the most successful groups of organisms present in almost all terrestrial habitats on the Earth. The published papers on ants with various sampling techniques were reviewed focusing on species richness along the elevational gradients to explain distribution patterns of ants and their potential drivers in the world. Pitfall trapping, hand collection, Winkler extractor and bait traps were found common sampling techniques for ant studies. Based upon literature, five broad distributional patterns were identified viz. mid-elevation peaks, decreasing, increasing, low plateaus, and constant patterns along the elevation ranging from 0 to 4800 m above sea level. The mid-elevation peak was a common pattern. However, ant species richness of Nepal follows a decreasing pattern based on the available records. Temperature was found as the major predictor of species richness patterns of ants.